Adolescent male soccer players have higher growth rates and risk of injury is associated with biological maturity - Dut, Raziye; Akgül, Sinem; Dönmez, Gürhan; Ulkar, Bülent; Kanbur, Nuray; Derman, Orhan (The Turkish Journal of Pediatrics, 2023)
Background. The objective of this study was to ascertain disparities in growth and maturation between male adolescents engaged in soccer and their non-athletic counterparts, as well as to examine the injury features specific to young soccer players. Methods. A total of 206 soccer players between the ages of 11-16 years, and 208 non-athletic peers were enrolled. Height, weight, body mass index (BMI), annual growth rate, and skeletal age evaluated using a left handwrist x-ray were determined. Biological and sexual maturation were evaluated using skinfold thickness, body composition, and Tanner stages. The game positions, initial age for playing soccer, the number of games per/ week, the number of sports injuries, date of injury, duration for return to activity, the site, nature, mechanism, and rate of injury were recorded for soccer players. Using an injury card, the characteristics of soccer player injuries were recorded. Results. The mean age of the participants was 13.6 ± 1.5 years. There was no difference in the growth rates between the groups at the ages of 11.0, 12.0, and 15.0 but at the ages of 13.0 and 14.0 years growth rates were higher in the soccer group. The soccer players were taller than the controls. For all Tanner stages, soccer players had a lower BMI and total body fat percentage, as well as a faster growth rate. Injuries occurred at a rate of 39.3% per year among soccer players. The most common being toe injuries, and playing soccer increased the risk of multiple injuries. Additionally, injuries occurred more frequently in soccer players who were taller, heavier, with higher total body fat and/or higher growth rate, and most commonly occurred during Tanner stage 4. Futhermore, Tanner stage 4 had a higher incidence of two or more injuries than the other stages. Conclusions. Adolescent male soccer players have higher growth rates than their non-athletic peers, and their biological maturity status is associated with an increased risk of injury.